Asymptotic representation of the perron root of a matrix-valued stochastic evolution - Yeleyko, Ya. I.; Shurenkov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study an asymptotic representation of the Perron root of a matrix-valued stochastic evolution given by the transport equation.